Differential Efficacy of Digital Scaffolding of Numeracy Skills in Kindergartners With Mild Perinatal Aversities - Merkelbach, Inge; Plak, Rachel D.; Jong, Maria T. Sikkema-de; Rippe, Ralph C.A. (Frontiers in Education, 2022)
Introduction: Children who experienced mild perinatal adversity (i.e., born late preterm or small for gestational age) are at increased risk for delays in early numeracy and literacy, which increases inequality in educational opportunities. However, this group showed increased susceptibility to the characteristics of their educational environment for literacy, especially for those born late preterm. Intervening in this group may thus be particularly beneficial, provided that their educational environment is highly structured. Delays in numeracy and mathematics are most firmly acknowledged in these children. It remains unclear if these children are also more susceptible to their educational numeracy environment. We test the hypothesis of increased susceptibility to characteristics of their educational environment in the field of numeracy. Methods: We tested the efficacy of a digital intervention of two to three months, which focused on visual spatial skills in a large randomized controlled trial in a sample of five-to-six-year-old kindergarten pupils from 140 elementary schools. About 45% of all participants showed delays in numeracy, of whom n=67 (11%) were born late preterm, n=157 (26%) were born small for gestational age, and n=389 (63%) had no mild perinatal adversities. Pupils were assigned to a guiding and structured intervention focused on visual spatial skills (n=294) or a control program (n=319), targeting literacy skills. Results: The intervention did not show a main effect. The program was not effective in children small for gestational age, but it was for children born late preterm (Cohen’s d = .71, CI = .07 - 1.36), showing stronger numeracy skills compared to term-born peers in the intervention condition. Early numeracy skills in children born late preterm fell behind compared to term-born peers in the control condition. Conclusion: A highly structured educational numeracy environment, using repetition and adaptive feedback benefited early numeracy skills of late preterm children. These children outperformed their peers in early numeracy skills, while those in the control condition fell behind. Findings align with earlier findings on promoting early literacy in this group through an equivalent literacy intervention. A relatively simple and cost-effective intervention thus may help reduce the risk of educational inequality for children born late pre-term.